The emergence of Inter-Asian Law: normative origins, trajectories, and contours - Erie, M; Lin, C-F (Oxford Business Law Blog, 2023)
What if Anglo-American common law and European civil law are no longer the only referents for legal development and innovation in the world? This question is addressed in the forthcoming volume Inter-Asian Law, edited by Matthew S. Erie and Ching-Fu Lin, to be published by the Cambridge University Press’s Studies in Comparative Law series, and featuring sixteen chapters by leading legal scholars from Asia and beyond. This edited volume is the first to present an analytical framework for the new field of ‘Inter-Asian Law’ (IAL). It draws on papers presented at the IAL workshop, December 16 & 17, 2022, National Tsing Hua University, Taiwan.